2020
DOI: 10.1584/jpestics.d19-076
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of flutianil as a novel fungicide against powdery mildew

Abstract: Flutianil, chemically characterized as a cyano-methylene thiazolidine, showed antifungal activity against powdery mildew on various crops but not any other plant pathogens tested. Flutianil showed high residual and translaminar activities and rainfastness against Podosphaera xanthii. It also exhibited curative activity against P. xanthii on cucumber at an extremely low concentration of 10 mg/L. There was no cross-resistance between flutianil and other existing fungicides. Morphological studies revealed that fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our previous report indicated that in the infection process of Bgh, flutianil inhibited the haustorial formation and the prevention of pathogen nutrient acquisition from the host cells. 13) In current studies, the most noteworthy morphological and ultrastructural changes as a result of treating Bgh with flutianil were in the haustoria. Flutianil causes the EHMa to be obscured, resulting in the HCW being obscured.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Our previous report indicated that in the infection process of Bgh, flutianil inhibited the haustorial formation and the prevention of pathogen nutrient acquisition from the host cells. 13) In current studies, the most noteworthy morphological and ultrastructural changes as a result of treating Bgh with flutianil were in the haustoria. Flutianil causes the EHMa to be obscured, resulting in the HCW being obscured.…”
Section: Discussionmentioning
confidence: 51%
“…Our previous study indicated that on flutianil-treated leaves, conidiophores had formed abnormally as elongated tubes, but the collapse of conidiophores or mycelia was not observed. 13) These findings indicate that the morphological change in Bgh by treatment with flutianil is completely different from that by treatment with the existing fungicides cyflufenamid and metrafenone.…”
Section: Comparison Of the Effect Of Flutianil With That Of Other Exist-mentioning
confidence: 92%
See 1 more Smart Citation